UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PPKN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TANDUR DI KELAS X IPS 1 SMAN 11 PONTIANAK - Selvia, Selvia; Sulistyarini, Sulistyarini; Purnama, Shilmy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to improve students critikal thinking skills in civics subjects by using the TANDUR learning model in class X IPS 1 SMAN 11 Pontianak, which is carried out in 2 cycles. The research method used is qualitative in the from of classroom action research. The subjects in this study were 24 students of class X IPS 1 SMAN 11 Pontianak, tataling 24 students. Data collection techniques include tests, observations, and questionnaires. Questionnaires, tes sheets, and observation sheets are the instruments used to collect data. The instruments used to collect data are in the from of tests including initial tests, first cycle tests, second cycle tests, final tests, teacher ability observation sheets, and student activity observation sheets. Data from test results and observation sheets were analyzed qualitatively and quantitatively. The results showed that the critical thinking ability of students in the first cycle was 61.97%, then in the second cycle increased to 78.12%, and in the final test increased to 87.5%. Given that students critical thinking skills grow in each cycle, it can be said that the TANDUR learning model can help students. In the vontext of applying the TANDUR learning model to learning Civics subjects and other subjects.